Africa's Pulse, No. 21, Spring 2020 : An Analysis of Issues Shaping Africa’s Economic Future - Zeufack, Albert G.; Calderon, Cesar; Kambou, Gerard; Djiofack, Calvin Z.; Kubota, Megumi; Korman, Vijdan; Cantu Canales, Catalina (World Bank, Washington, DC, 2020)
The COVID-19 pandemic has taken a toll on human life and brought major disruption to economic activity across the world. Despite a late arrival, the COVID-19 virus has spread rapidly across Sub-Saharan Africa in recent weeks. Eeconomic growth in Sub-Saharan Africa is projected to decline from 2.4 percent in 2019 to -2.1 to -5.1 percent in 2020, the first recession in the region in 25 years. The coronavirus is hitting the region’s three largest economies —Nigeria, South Africa, and Angola— in a context of persistently weak growth and investment. In particular, countries that depend on oil and mining exports would be hit the hardest. The negative impact of the COVID-19 crisis on household welfare would be equally dramatic. African policymakers need to develop a two-pronged strategy of “saving lives and protecting livelihoods.” This strategy includes (short-term) relief measures and (medium-term) recovery measures aimed at strengthening health systems, providing income support to workers and liquidity support to viable businesses. However, financing of these policies will be challenging amid deteriorating fiscal positions and heightened public debt vulnerabilities. Therefore, African countries will require financial assistance from their development partners -including COVID-19 related multilateral assistance and a debt service stand still with official bilateral creditors.